Synthesis, Characterization and Host-Guest Complexation of Asplatin: Improved In Vitro Cytotoxicity and Biocompatibility as Compared to Cisplatin - Sherif Ashraf Fahmy; Fortuna Ponte; Giulia Grande; Iten M. Fawzy; Asmaa A. Mandour; Emilia Sicilia; Hassan Mohamed El-Said Azzazy (MDPI AG, 2022)
Para-sulfocalix[n]arenes are promising host molecules that can accommodate various chemotherapeutic drugs. Pt(IV)-based complexes, including satraplatin and asplatin, are promising alternatives that overcome the shortcomings of Pt(II) complexes. In this study, asplatin has been synthesized by fusing acetylsalicylic acid (aspirin) and cisplatin. Furthermore, it has been characterized using 1H NMR, mass spectrometry, elemental analysis, and UHPLC. A host-guest complex of asplatin and p-sulfocalix[4]arene (PSC4) has been developed and characterized using UV, Job's plot analysis, HPLC, and density functional theory (DFT) calculations. The experimental and computational investigations propose that a 1:1 complex between asplatin and PSC4 is formed. The stability constant of the designed complex has been determined using Job's plot and UHPLC and computed to be 9.1 × 104 M-1 and 8.7 × 104 M−1, which corresponds to a free energy of complexation of −6.8 kcal mol-1, while the calculated value for the inclusion free energy is −13.2 kcal mol−1. Both experimentally and theoretically estimated complexation free energy show that a stable host-guest complex can be formed in solution. The in vitro drug release study displayed the ability of the complex to release its cargo at a cancerous pH (pH of 5.5). Additionally, the asplatin/PSC4 complex is shown to be biocompatible when tested on human skin fibroblast noncancerous cells, demonstrating the highest in vitro cytotoxic activity against (MCF-7), cervical (HeLa), and lung cancer cells (A-549), with IC50 values of 0.75, 2.15, and 3.60 µg/mL, respectively. This is as compared to either cisplatin (IC50 of 5.47, 5.94 and 9.61 µg/mL, respectively) or asplatin (IC50 of 1.54, 5.05 and 3.91 µg/mL, respectively). On the other hand, the free asplatin exhibited higher cytotoxicity on cancerous cells and lower toxicity on noncancerous cells. The outcomes of the present joint theoretical and experimental investigation reinforce the interest in platinum-based anticancer therapeutics when they are protected from undesired interactions and suggest the use of the PSC4 macromolecule as a promising carrier for Pt(IV) anticancer drugs. The formed asplatin/PSC4 inclusion complex may represent an effective chemotherapeutic agent.